The Effectiveness of Using Saturated NaCl Solution, Sucrose, MgSO4, and ZnSO4 With Flotation Method for Examination of Soil Transmitted Helminth Infections in Elementary School Students - Sresta Azahra; Suhartini Suhartini; Fitri Nur Rica (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Worm infections are a neglected tropical disease. This infection infects humans and is caused by Soil Transmitted Helminth (STH) worms, consisting of Ascaris lumbricoides, Trichuris trichiura, and hookworms. Infection control with mass drug administration and infection monitoring with sensitive and specific diagnostic methods. One of the diagnostic methods is the flotation method using a solution of NaCl, MgSO4, sucrose, and ZnSO4. The study aimed to determine the effectiveness of the use of NaCl, MgSO4, sucrose, and ZnSO4 flotation methods for examination of STH infection in elementary school students. This study was analytic observational with cross sectional design. Samples were used elementary school students' faeces to performed macroscopic and microscopic examinations of NaCl, MgSO4, sucrose, and ZnSO4 solution flotation methods. The research data was analyzed using the Kruskal Wallis with SPSS 23.0. The results showed that the number of worm eggs using ZnSO4 solution was 935 worm eggs, the average was 62,33; saturated NaCl solution as many as 564 worm eggs, an average 37,60; MgSO4 as many as 267 worm eggs, an average of 17,80; and sucrose as many as 79 worm eggs, an average of 5,27. Statistical test results obtained p value> 0.05 (p = 0,610). The conclusion is ZnSO4 solution more effective for detecting STH egg flotation method although, statistical test there is no difference between various flotation solutions for STH eggs.Keywords: Worm infections; Soil Transmitted Helminth; worm eggs; flotation